Result-Oriented Education In The Development Of Technical Students' Skills - Timur Murodullayevich Xolmuxamedov (Genius Journals, 2024)
This article examines the acquisition of learning outcomes by technical school students and the necessity of a target educational process model.
Keywords: professional education; learning outcomes